Selling the real estate securing the privilege of the public treasury in a public auction A study in the UAE law - AL sandal, Mariam (Journal of Legal Sciences, 2023)
The concession rights established for the public treasury are returned to the debtor’s funds, whether they are real estate or movables, and they may be returned to a specific amount of these funds, in accordance with the relevant laws. The legislator in the United Arab Emirates, according to the general rules, did not stipulate that this right be registered with the competent real estate registration department. This may lead to the sale of the property securing the concession right of the public treasury without the knowledge of the competent department of the treasury department to claim this right. In selling by judicial public auction, the legislator requires certain procedures through which the real estate is purged of accessory real rights, including concession rights, and among these procedures is the announcement of the seizure decision to the owners of the restricted rights, and as a result of not registering the privilege of the public treasury, it will not be announced with seizure. At the end of the research, we reached results, including: that the privilege rights due to the public treasury fall within the scope of general privilege rights with a variable base, and their place may be all the debtor’s money, or a specific money from his money, movable or real estate, and the conditions and scope of the privilege of the public treasury and the funds that This right is contained in the special laws regulating this type of right. As for the most important recommendations, the UAE legislator recommended that it be necessary to stipulate within the special rules related to the privilege of the public treasury what indicates the transfer of the privilege to any other money from the debtor’s money in the event that it is limited to the real estate subject of implementation.